Ventricular tachycardia in ischemic heart disease substrates - Olujimi A. Ajijola; Roderick Tung; Kalyanam Shivkumar (Indian Heart Journal, 2014)
Advances in the treatment of myocardial infarction (MI) have improved survival after ischemic cardiac injury. Post-infarct structural and functional remodeling results in electrophysiologic substrates at risk for monomorphic ventricular tachycardia (MMVT). Characterization of this substrate using a variety of clinical and investigative tools has improved our understanding of MMVT circuits, and has accelerated the development of device and catheter-based therapies aimed at identification and elimination of this arrhythmia. This review will discuss the central role of the ischemic heart disease substrate in the development MMVT. Electrophysiologic characterization of the post-infarct myocardium using bipolar electrogram amplitudes to delineate scar border zones will be reviewed. Functional electrogram determinants of reentrant circuits such as isolated late potentials will be discussed. Strategies for catheter ablation of reentrant ventricular tachycardia, including structural and functional targets will also be examined, as will the role of the epicardial mapping and ablation in the management of recurrent MMVT.